"It gave me something big in my life to wonder and think about which took over the space … and not MS": managing well-being in multiple sclerosis through art-making. (July 2014) - Hunt, Laura; Nikopoulou-Smyrni, Panagiota; Reynolds, Frances
Abstract Background and aim: Individuals living with Multiple Sclerosis (MS) often face progressive loss of function, uncertainty and disruption to self-image and valued roles. Previous studies show that creative self-expression is valued by some people living with long-term illness, yet its meaning for people living with MS is unclear. This research study explored the meanings of leisure-based visual art-making for people living with MS. Method: This qualitative study followed guidelines for Interpretative Phenomenological Analysis (IPA). Single semi-structured interviews were conducted with five adults (2 males; 3 females; 40–65 years), recruited from MS Ireland. Findings: Participants valued art-making for contributing to a more satisfying way of life; for filling occupational voids and using time well. Deep immersion offered respite from worry about illness. Creative classes offered social camaraderie and opportunities for learning and development. Art-making processes and products were highly affirmative, increasing emotional well-being and promoting self-worth. Most felt that they expressed valued aspects of self through their art. Art-making appeared to assist with identity maintenance, accommodating functional losses associated with MS whilst opening "new doors". Conclusion: Art-making offered a multi-faceted means of supporting identity and increasing fulfilment in lives that were restricted in many ways by MS. Implications for Rehabilitation Creative leisure activities may offer people with MS a flexible means of using time and filling occupational voids increasing satisfaction and well-being. Art and craft classes may offer people with MS opportunities to socialise and provide a source of personal development. Deep immersion in creative activities may offer the experience of respite from worry about MS. Some people with MS are able to take up creative activities for the first time after the onset of illness and find them meaningful and supportive of well-being; at least minimal pre-illness interest in arts and crafts seems helpful to provide basic confidence and skills; availability of accessible, welcoming art classes also seems to encourage participation.